The impact of safety and health towards construction workforce productivity - Wong, Queenie; Noraina Mazuin, Sapuan; Ali Khan, Muhammad Waris (Universiti Malaysia Pahang, 2023)
The purpose of this research is to study the impact of safety and health towards construction workforce productivity among G3 contractor in Kuantan, Pahang. Previous research found that poor performance of time and budget, wastage in site and low productivity are mainly caused by the safety and health issues happen in construction industry. The lack of safety concern based on insufficient safety compliance and poor attitude towards safety. While poor safety measure on working environment and material storage causes injuries and accident that affect works in site. Lack of health concern base on physical health issue we discuss about respiratory illness and mental health issue about stress and burnout has found affect the most among construction workers. Quantitative research is used to collect data and analyse by using PLS-SEM model. The data has applied to test the hypothesis based on the research objective. This research has collected 152 responses from G3 contractor workers in Kuantan, Pahang. Hence, the result of this survey is slightly limited but it could be used as a reference for future study base on safety and health topic.